Second and Third Cardiac Valve Reoperations: Factors Influencing Death and Long-Term Survival - Toker, Mehmet Erdem (Texas Heart Institute, 2009)
We retrospectively investigated preoperative and postoperative characteristics in order to determine factors that affected hospital death in patients who underwent 3 or 4 separate cardiac valvular surgeries. The hospital records of 53 such patients who were operated upon from 1985 through 2006 were obtained. The patients were divided into 2 groups according to whether their initial operation was a closed mitral commissurotomy (group C, n = 33) or open-heart surgery with cardiopulmonary bypass (group O, n = 20). In group C, all patients who had initially undergone 1 or 2 closed mitral commissurotomy procedures underwent subsequent reoperations that entailed median sternotomy and cardiopulmonary bypass. Sternotomy and cardiopulmonary bypass had been used in valvular operations of all group O patients. The total early mortality rate was 11.3% (6 of 53 patients). Multivariate analysis revealed that longer aortic cross-clamp times and double valve replacement at last operation significantly increased the risk of death. Herein, we discuss our conclusion that 3rd or 4th cardiac valvular operations incurred acceptable early postoperative mortality rates.